Which orthopaedic trauma patients are likely to refuse to participate in a clinical trial? A latent class analysis - Nathan N O’Hara; Robert V O’Toole; Renan Castillo; C Daniel Mullins; Yasmin Degani; Debra Marvel; David Wells; Stephen Wegener; Katherine Frey; Tara Joseph; Stephen Breazeale; Randolph Fenninger; et al. (BMJ Open)
Objective The study aimed to assess systematic differences in the characteristics of patients that consented for the trial compared with the broader pool of eligible patients in a large, pragmatic orthopaedic trauma trial.Design A retrospective observational study performed from April 2017 to March 2018.Setting Academic trauma centre in Baltimore, USA.Participants There were 642 eligible adult trial participants with an operative fracture to the appendicular skeleton and were indicated for blood clot prophylaxis. The median age of the sample was 50 years (IQR: 31–63), and 60% were male.Primary outcome measure The primary outcome was the refusal to enrol in the trial. Demographic and injury covariates were included in iterations of latent class models. The final model was selected based on a minimum Bayesian information criterion.Results The final model identified three clusters with five covariates predictive of cluster membership (age, neighbourhood-based socioeconomic status, alcohol use, multiple fractures, multiple surgeries). The three clusters were associated with 22% (Cluster 1), 38% (Cluster 2) and 62% (Cluster 3) refusal rates, respectively. Members of Cluster 3 (n=84) were most commonly between 66 and 80 years of age (49% vs 6% (Cluster 1) and 21% (Cluster 2)), of high neighbourhood-based socioeconomic status (85% vs 63% (Cluster 1) and 8% (Cluster 2)), with isolated fractures (100% vs 80% (Cluster 1) and 92% (Cluster 2)), and were less likely to have multiple surgeries compared with the other clusters (28% vs 47% (Cluster 1) and 35% (Cluster 2)).Conclusion In this study, the likelihood of refusing to participate in the trial ranged from 22% to 62% in the three identified clusters. Elderly age, high socioeconomic status, and less severe injuries defined the cluster that was most likely to refuse trial participation.Trial registration number NCT02984384.